Antiplasmodial Activity of Medicinal Plant Preparations T610 and S076 Using Plasmodium Falciparum in Vitro Culture System - Appiah-Opong, R. (University of Ghana, 2001)
Some traditional medical practitioners use decoctions of the plants Tridax procumbens and Phyllanthus amarus, separately, to treat malaria in Ghana. These plants have however, not been investigated scientifically to establish their antimalarial activities. In this study, inhibition of chloroquine-resistant Plasmodium falciparum uptake o f 3H-hypoxanthine was used as an in vitro assay to assess the antiplasmodial activities of aqueous, ethanolic, chloroform and ethyl acetate extracts of Tridax procumbens and Phyllanthus amarus. Chloroquine was used as a reference antimalarial drug. Cytotoxicities of the extracts to red blood cells were also investigated. Furthermore, the aqueous extracts of the plants were evaluated for haem polymerisation inhibitory activity. The results show that high concentrations of chloroquine inhibited the uptake of 3Hhypoxanthine by Plasmodium falciparum, confirming the chloroquine-resistant nature of the parasites used. Both plant extracts also demonstrated antiplasmodial activity against the chloroquine resistant plasmodial parasites. Among the various extracts, the lowest 50% inhibitory concentrations (IC50) of 24.8 and 11.7 |ig/ml corresponded to the aqueous and ethanolic extracts, respectively, of Phyllanthus amarus. For Tridax procumbens, the lowest IC50 values were 225.0 and 143.4 |J.g/ml for the ethanolic and aqueous extracts, respectively. Unlike chloroquine, none of the extracts inhibited haem polymerisation. Within the concentration range used, the least cytotoxicity to RBCs was observed in the aqueous extracts of both plants, the ethanolic extract of Phyllanthus amarus and the ethyl acetate extract of Tridax procumbens. These results suggest that the aqueous and ethanolic extracts of both plants were more effective as antiplasmodial preparations than the other extracts.
MPhil. Biochemistry
Keywords: Medicinal Plant; Vitro Culture System; Antiplasmodial Activity; Traditional Medical Practitioners